Teacher’s Perspective on DeepL in Learning EFL Writing - Aurelia Ratna Erviyanti (Universitas Pendidikan Ganesha, 2025)
In order to ensure that technology is used correctly and to its full potential in the classroom, teachers play a critical role. In English as a Foreign Language (EFL) classrooms, it is essential to understand the factors that shape how teachers use and supervise the use of Machine Translation (MT) tools, such as DeepL, to enhance students' writing skills. To meet the objectives of this study, researchers analyzed fifteen empirical research articles from peer-reviewed journals published between 2020 and 2025, sourced from Google Scholar. This study revealed five main themes: (1) DeepL can improve the quality of students' writing. (2): DeepL might helping people acquire second languages (3)Teachers struggle to fulfill their responsibilities as facilitators (4) Teachers are concerned about over-reliance on DeepL; and (5) DeepL does not have an impact on students' writing skills The study offers beneficial strategies that teachers can use to easily integrate DeepL, ensuring it enhances instead of replacing standard written education.